THE IMPACT OF DIGITAL MEDIA ON LANGUAGE EVOLUTION (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT The rise of digital media has profoundly influenced language evolution, transforming how we communicate, write, and interact. Social media platforms, texting, blogs, and online forums have given birth to new linguistic forms, such as acronyms, emojis, and internet slang, which have quickly permeated everyday language. This paper explores the role of digital media in shaping language through the creation of hybridized forms, the acceleration of language change, and the increased influence of global communication. Digital media has facilitated the spread of informal language, making it more accessible and acceptable in traditionally formal contexts. Additionally, digital platforms enable rapid linguistic innovation, with new words and expressions often emerging and gaining widespread use in a matter of days. However, the impact of digital media on language is not entirely beneficial, as some argue it may lead to language fragmentation, the erosion of grammar, and the loss of regional dialects. The paper also examines the consequences of language standardization and the potential effects on linguistic diversity. Overall, the interplay between digital media and language evolution highlights the dynamic nature of language, shaped by technological, cultural, and social forces, as it adapts to the demands of a digital, interconnected world.